MgCO? contents, structure, and carbon and oxygen isotope compositions of fibrous crystals in a Miocene methane seep carbonate - Yang Lu; Carsten Paulmann; Boriana Mihailova; Thomas Malcherek; Daniel Birgel; Matthias López Correa; Zhiyong Lin; Liuyi Lu; Yvonne Milker; Jörn Peckmann (PANGAEA, 2023)
Primary fibrous dolomite has been reported in cavity systems in Neoproterozoic reefal and platformal carbonates. It is surprising to find fibrous dolomite in Miocene methane seep carbonates from Marmorito, northwest Italy. To study the formation of the fibrous crystals, we selected points of interest and measured the main compositions, MgCO? contents, structure and carbon and oxygen isotope compositions in 2021. Main compositions were analysed by energy-dispersive X-ray spectroscopy equipped with a scanning electron microscope. The MgCO? contents were obtained from Raman spectroscopy and electron probe microanalysis. Structures of the fibrous crystals were measured by synchrotron X-ray diffraction. Carbon and oxygen isotope compositions were determined by a gas isotope ratio mass spectrometer. The results suggest that the fibrous crystals in the Marmorito seep carbonates were directly formed from pore water dominated by sulphate-driven anaerobic oxidation of methane. Their formation conditions help to constrain the formation conditions of the Neoproterozoic counterparts.